Bea Wolf - Weinersmith, Zach, 1982-; Boulet, 1975- (New York, NY : First Second, 2023)
"Listen! Hear a tale of mallow-munchers and warriors who answer candy's clarion call! Somewhere in a generic suburb stands Treeheart, a kid-forged sanctuary where generations of tireless tykes have spent their youths making merry, spilling soda, and staving off the shadow of adulthood. One day, these brave warriors find their fun cut short by their nefarious neighbor Grindle, who can no longer tolerate the sounds of mirth seeping into his joyless adult life. As the guardian of gloom lays siege to Treeheart, scores of kids suddenly find themselves transformed into pimply teenagers and sullen adults! The survivors of the onslaught cry out for a savior--a warrior whose will is unbreakable and whose appetite for mischief is unbounded. They call for Bea Wolf."--Provided by publisher.
A modern middle-grade graphic novel retelling of Beowulf, featuring a gang of troublemaking kids who must defend their tree house from a fun-hating adult who can instantly turn children into grown-ups.
Print version record.
Keywords: Beowulf, -- King of the Geats -- Comic books, strips, etc; Children -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Beowulf, -- King of the Geats -- Juvenile fiction; Children -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Heroes -- Juvenile fiction; Beowulf -- Adaptations; Beowulf -- Adaptations; Children -- Fiction; Heroes -- Fiction; Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Beowulf, -- King of the Geats; Beowulf; Children; Heroes; Quests (Expeditions); Adaptations; Comics (Graphic works); Fantasy comics; Fiction; Graphic novel adaptations; Graphic novels; Humorous comics; Juvenile works; Fantasy comics; Humorous comics; Graphic novel adaptations; Comics (Graphic works); Graphic novels; Adaptations en romans graphiques